PERAN PERPUTARAN PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS - Nurul Qhasanah (LPMP Imperium, 2019)
This study aims to analyze the relationship between inventory turnover and sales growth on profitability. The research data is the financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2014 - 2018, using a purposive sampling method obtained by 23 companies. Data analysis using panel data regression with the help of the EVIEWS program. The results show that inventory turnover and sales growth are two important components that can affect company profitability. The implications and limitations are explained in this article.